Kawasaki Shock Syndrome in a 12-Year-Old Girl Mimicking Septic Shock - Vindika Prasad Sinhabahu; Janani Suntharesan; Dimuthu Saraji Wijesekara (Case Reports in Infectious Diseases)
Kawasaki disease is diagnosed when fever lasts for more than 5 days with the presence of four out of five of the following clinical features: bilateral conjunctival congestion, changes in the lips and oral cavity, polymorphous exanthem, changes in peripheral extremities, and acute nonpurulent cervical lymphadenopathy (Nakamura et al., 2012). The average age of onset is 2 years and 90% of patients are below 5 years of age. Boys are more affected than girls (Cox and Sallis, 2009). This case report describes an adolescent female who was initially managed as having septic shock and subsequently found to have Kawasaki shock syndrome.